Strategi Pengembangan Wisata Edukasi Gurami dalam Meningkatkan Ekonomi melalui Metode ABCD - Shita Devita Nur Illahi (Amaluna: Jurnal Pengabdian Masyarakat, 2023)
Abstract: The Gurami Seduri Tourism is a local attraction initially formed by the Community-Aware Tourism Group, consisting of approximately six members who initiated community empowerment through educational tourism located in Seduri Wonodadi, Blitar. This research employs the Asset-Based Community Development (ABCD) method, which is an approach in empowering and enhancing the quality of human resources. The results of this dedication increase awareness within the Gurami Seduri Tourism Awareness Group through socialization activities, incorporating the implementation of Law Number 6 of 2014. The tourism group adopts a conscious economic guideline, serving as a pillar in creating a smart village. Gurami Seduri Educational Tourism should undergo continuous improvement for its sustainability, particularly among its members. The success of the balancing strategy in Gurami Seduri Tourism, in a broader sense, can reflect the values of community empowerment. Internal analysis of its management includes performance analysis, such as culinary services with various Gurami dishes and education on Gurami cultivation. External analysis involves managing all members, both internally and externally, building networks with relevant policy stakeholders, and forming partnerships in the management of local tourism in Blitar, such as local guides, tourism awareness groups, and other communities.